Farm shows come back - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
A long-standing favourite in many farmers diaries in Malawi as elsewhere, agricultural shows fell out of favour with government backers during the 1990 s. Now though, it is the farmers themselves in Malawi s southern district of Mulanje who have...